Customizable Implant-specific and Tissue-Specific Extracellular Matrix Protein Coatings Fabricated Using Atmospheric Plasma - Tan, Fei; Al-Rubeai, Mohamed (Frontiers in Bioengineering and Biotechnology, 2019)
Progression in implant science has benefited from ample amount of technological contributions from various disciplines, including surface biotechnology. In this work, we successfully used atmospheric plasma to enhance the biological functions of surgical implants by coating them with extracellular matrix proteins. The developed collagen and laminin coatings demonstrate advantageous material properties. Chemical analysis by XPS and morphological investigation by SEM both suggested a robust coating. Contact angle goniometry and dissolution study in simulated body fluid elicited increased hydrophilicity and physiological durability. Furthermore, these coatings exhibited improved biological interactions with human mesenchymal and neural stem cells. Cell adhesion, proliferation, and differentiation proved markedly refined as shown by enzymatic detachment, flow cytometry, and ELISA data, respectively. Most importantly, using the pathway-specific PCR array, our study discovered dozens of deregulated genes during osteogenesis and neurogenesis on our newly fabricated ECM coatings. The coating-induced change in molecular profile serves as a promising clue for designing future implant-based therapy. Collectively, we present atmospheric plasma as a versatile tool for enhancing surgical implants, through customizable implant-specific and tissue-specific coatings.